Pengaruh Penerapan Green Accounting terhadap Profitabilitas Perusahaan: Studi Kasus Pabrik Roti Monasqu, Desa Gilang, Kec. Ngunut, Kabupaten Tulungagung tahun pembukuan 2015-2021 - Enggar Ayu Romadloni; Dyah Pravitasari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to describe how the effect of implementing Green Accounting (Accounting. Environment) on the level of Profitability (ROA) at the Monasqu Bakery Company in Ngunut District, Tulungagung Regency within a period of seven years (2015-2021). Research Methodology: In this study, the method used is Multiple Linear Regression Analysis, using the research object of the company's financial statements and environmental cost reports in 2015-2021. The study used a data sample of 30 samples. Result: With the result that the application of Environmental Cost Accounting has a significant effect on the profitability (ROA) of the Monasqu Bread Factory. Limitation: Data collection as a research sample focused on the nominal level of net profit on sales and environmental costs incurred by the Monasqu factory during 2015-2021. Which sample is a basic sample that almost every manufacturing company has, both simple and complex. Contribution: so that it is hoped that this research can be used as a reference in further research in other manufacturing companies, especially in the Ngunut District, and generally in Tulungagung Regency.